Bink & Gollie - DiCamillo, Kate.; McGhee, Alison, 1960-; Fucile, Tony (Somerville, Mass. : Candlewick Press, 2010)
Two roller-skating best friends--one tiny, one tall--share three comical adventures involving outrageously bright socks, an impromptu trek to the Andes, and a most unlikely marvelous companion.
Wilson's Children, September 2011.
School Library Journal, August 2010.
Pub Weekly, August 2010.
Kirkus Starred, August 2010.
Booklist, September 2010.
New York Times, November 2010.
Keywords: Friendship -- Juvenile fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Adventure fiction; Humorous fiction; Adventure fiction; Humorous fiction